X-ray Tomographic Investigation of Water Distribution in Polymer Electrolyte Membrane Fuel Cells with Different Gas Diffusion Media. (29th August 2016) - Alrwashdeh, Saad Sabe'; Markötter, Henning; Haußmann, Jan; Scholta, Joachim; Hilger, André; Manke, Ingo
Abstract : In this study, water transport in polymer electrolyte membrane fuel cells (PEMFCs) is investigated by synchrotron X-ray tomography. The measurement technique is used to reveal the relationship between the structure of the gas diffusion media (GDM) and the water distribution. It is shown how the water distribution and transport is visualized and quantitatively analyzed. We present investigations on three different GDM: A GDM with a modified microporous layer (MPL), a thick GDM with limited back diffusion and a reference material.